Decentralized static output feedback controller design for linear interconnected systems - Fadhilah, Helisyah Nur; Adzkiya, Dieky; Arif, Didik Khusnul; Zhai, Guisheng; Mardlijah (Zielona Góra: Uniwersytet Zielonogórski)
Many interconnected systems in the real world, such as power systems and chemical processes, are often composed of subsystems. A decentralized controller is suitable for an interconnected system because of its more practical and accessible implementation. We use the homotopy method to compute a decentralized controller. Since the centralized controller constitutes the starting point for the method, its existence becomes very important.
Keywords: output feedback; decentralized controller; homotopy method; interconnected systems; matrix inequality